Potassium Application Increases Cotton (Gossypium hirsutum L.) Fiber Length by Improving K+/Na+ Homeostasis and Potassium Transport Capacity in the Boll-Leaf System under Moderate Salinity - Junjun Zhu; Liyuan Sun; Feiyan Ju; Zhuo Wang; Cai Xiong; Huilian Yu; Kai Yu; Yuyang Huo; Wajid Ali Khattak; Wei Hu; Shanshan Wang; Zhiguo Zhou; et al. (Agronomy, 2022)
Cotton has a high salt tolerance. However, due to the high salt content and low K+/Na+ ratio in saline soils, cotton yield and fiber quality are difficult to improve. To investigate the effects of potassium (K) on cotton fiber length under salt stress, a two-year bucket-based field experiment was conducted using two different cultivars (CCRI 79, salt tolerant, and Simian 3, salt sensitive). Three K rates (K0, 0 kg K2O ha−1; K150, 150 kg K2O ha−1; and K300, 300 kg K2O ha−1) were applied at low, middle, and high soil electrical conductivities (S1, 1.7–1.8 dS m−1; S2, 6.4–6.9 dS m−1; and S3, 10.6–11.8 dS m−1) to investigate the absorption, transport, and distribution characteristics of K+ and Na+ in the boll-leaf system (including the leaf subtending the cotton boll (LSCB), fruiting branch, boll shell, and fiber) of both cotton cultivars, as well as the relationship with fiber length. The results showed that K application (K150 and K300) significantly increased the cotton fiber length under salt stress, with the largest fiber length alleviation coefficients (AC) in the middle fruiting branches. The AC decreased with an increase in salt stress and was greater in CCRI 79 than in Simian 3. The K150 treatment (soil K+/Na+ = 1/13) completely mitigated the reduction in fiber length caused by S2 salt stress in CCRI 79, whereas the K300 treatment (soil K+/Na+ = 1/10) completely eased the reduction in fiber length caused by S2 salt stress in Simian 3. An application of K under salt stress increased the K+ content and K+/Na+ ratio in the soil and the organs of the boll-leaf system, regulated the K+/Na+ homeostasis in the boll-leaf system, enhanced the K+-selective transport coefficient (SK-Na) in the LSCB, maintained a high K+/Na+ ratio in the fiber, and mitigated the fiber length reduction. In conclusion, the fiber length reduction in salt-tolerant cultivars was completely mitigated by K150 (i.e., soil K+/Na+ = 1/13) under moderate salt stress; however, it was not completely mitigated by K application under high salt stress.